Debate Forum: preventing the extinction of the Sumatran rhinoceros - Abdul Hamid Ahmad; Junaidi Payne; Zainal Zaharu Zainuddin (Andalas University, 2013)
Sumatran rhino (SR), Dicerorhinus sumatrensis, represents one the oldest surviving mammal genera. Due to its role in traditional Chinese medicines, the horn of SR has been sought for well over a millennium and for many years the price of SR horn by weight rivalled that of gold. Extensive hunting lead to a precipitous decline in distribution and numbers of SR, particularly during the first decades of the twentieth century (van Strien, 1975) and it seems little short of a miracle that the species is not already extinct. By the mid twentieth century, the species was depleted from its former range and in danger of extinction in Malaya and Borneo (Hubback, 1939; Metcalf, 1961; Medway, 1977; Rookmaaker, 1977), and elsewhere on mainland Asia (Harper, 1945). Flynn and Abdullah (1984) suggested 52-75 SR roamed Peninsular Malaysia in the early 1980s, including 20- 25 individuals in the Endau-Rompin area, while Davies and Payne (1982) estimated 15-30 SRs in Sabah. By 1981, the only clear evidence of periodic breeding in wild SR in Malaysia was in Endau-Rompin and the Tabin area of eastern Sabah. At that time, the species was disappearing rapidly from the 20 or more locations where it had been present just a few decades earlier (Payne, 1990). Zainal Zahari (1995) found evidence of only five SRs, all adults, in Endau-Rompin by 1995, showing that published estimates of SR numbers were notoriously unreliable, and that actual numbers had declined by half over the preceding decade. The 1995– 1998 Global Environment Facility-UNDP Sumatran Rhinoceros Conservation Strategy project saw SR numbers declining still further, but inflated numbers kept appearing in public domain, largely due to some proponents’ disbelief that two decades of effort had failed. Zainal Zahari et al. (2001) plotted the disastrous decline of large mammals in Peninsular Malaysia from 1975-99.